A Case Report on Mutrashmari(Vesicle Calculus): Combining Suprapubic Cystolithotomy and Ayurvedic Management - Dr Hemanshu Maheta,; Dr Chandrakant Pawar,; Dr Shailesh jaiswal, (The Bioscan, 2026)
Introduction:A 52-year-old male presented with a 2-day history of pain, burning during micturition, increased frequency, and dribbling of urine, alongside occasional constipation. Investigations revealed a large urinary bladder stone and cystitis. The patient was diagnosed with Mutrashmari(vesical calculus) with associated cystitis.Case Presentation:The patient, a 52-year-old male, complained of pain and burning during urination, along with increased frequency and dribbling of urine for the past 2 days. He also had occasional constipation but no history of similar urinary issues or other systemic diseases like hypertension or diabetes. Ultrasound revealed a large bladder stone (33 mm) and cystitis. The patient was diagnosed with Mutrashmariand planned for surgical management.Management:The patient underwent suprapubic cystolithotomy under spinal anesthesia. Intraoperative procedures included a 5 cm suprapubic incision, identification of the bladder, and stone removal through bladder fundus incision. The bladder was closed in double layers, and appropriate hemostasis was achieved. Post-operatively, Ayurvedic interventions were initiated to support recovery: Internal medications: Gokshuradi Guggulu, Punarnavashtak kwath, Chandraprabha Vati, and Erandbhrusta Haritaki.Dietary modifications: Vata-pacifying foods, adequate hydration, and avoidance of spicy foods.Drain placement was performed to manage any residual secretion.Results:The patient tolerated the surgery well, with stable post-operative recovery. The Ayurvedic medications and lifestyle modifications were initiated to support healing and prevent recurrence of vesical calculus. Post-operative follow-up showed no complications. Conclusion:This case highlights the effective management of Mutrashmari(vesical calculus) through a combination of modern surgical intervention (suprapubic cystolithotomy) and Ayurvedic support. The prognosis is favorable, with no recurrence expected if appropriate Ayurvedic and dietary guidelines are followed.